CORTICOSTEROID-REFRACTORY SECONDARY IMMUNE THROMBOCYTOPENIA (ITP) ASSOCIATED WITH COVID-19 INFECTION: A CASE REPORT OF SUCCESSFUL RITUXIMAB SALVAGE THERAPY - Ari Christy Muliono; Adhiwidnya Ananta (JURNAL WIDYA MEDIKA, 2026)
Immune thrombocytopenia (ITP), also known as immune thrombocytopenic purpura, is classified into two types: primary and secondary. Secondary ITP has numerous causes, one of which is COVID-19. While research on COVID-19 was extensive during the 2019–2022 pandemic, particularly regarding its role in triggering secondary conditions, cases of COVID-19-induced secondary ITP remain underreported. Although current COVID-19 cases typically present with milder symptoms, it remains a crucial differential diagnosis in the post-pandemic era. This case report aims to provide insight into steroid-resistant secondary ITP resulting from a COVID-19 infection.